Analisis Peluang dan Tantangan Menggunakan Aplikasi Gojek atau Grabfood Bagi Pengembangan UMKM di Kota Palangkaraya - Mutia Angelina Sari; Dedi Takari (Jurnal Syntax Admiration, 2024)
This study aims to analyze the opportunities and challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in utilizing the Gojek and Grabfood applications in Jekan Raya District, Palangka Raya City. The method used is a mixed approach with surveys and in-depth interviews with MSME owners. The results show that this application provides significant opportunities, such as wider market access and reduced marketing costs. However, challenges in the form of fierce competition, high commission costs, and technological limitations are also faced by MSME actors. This study recommends technology training and community collaboration as strategic steps to maximize the potential of MSMEs.